Answer:4
Step-by-step explanation: Because 4 goes in 3/4 better and more eqvilent to that answer.
Answer:
f(-3) = 16
Step-by-step explanation:
Given:
f(x) = 2x² + x + 1
Required:
f(-3)
Solution:
Substitute x = -3 into f(x) = 2x² + x + 1
f(-3) = 2(-3)² + (-3) + 1
f(-3) = 2*9 - 3 + 1
f(-3) = 18 - 3 + 1
f(-3) = 16
P+5= -2
p= -7 ( I subtracted 5 to both sides of the equation)
Answer:
Step-by-step explanation:
If the new fraction is 8/12 I will show how to find it.
Let's say the original denominator is x, then the numerator is x-4, so we have (x-4)/x.
Then it says f we add 4 to both, so now we have x/(x+4) this equals 8/12. Now, keep in mind -4 cannot be an answer because it would make x/(x+4) be divided by 0 which wouldn't exist.
Now we just use algebra.
x/(x+4) = 8/12
12x = 8(x+4)
12x = 8x + 32
4x = 32
x = 8
So the original fraction (x-4)/x = (8-4)/8 = 4/8
Here you go, sometimes, quizlet is there with just the right info. Ur welcome.